'It's heavy, intense, horrendous and nice': clients' experiences in two-chair dialogues. (3rd April 2018) - Stiegler, Jan Reidar; Binder, Per-Einar; Hjeltnes, Aslak; Stige, Signe Hjelen; Schanche, Elisabeth
ABSTRACT: In this study, we conducted qualitative in-depth interviews to explore how clients experienced working with emotional processing and self-criticism in a two-chair dialogue intervention. Eighteen clients scoring high on self-criticism were interviewed upon completion of a short-term treatment (10–14 sessions) with Emotion-Focused Therapy (EFT), where the two-chair dialogue was used as the main intervention. A hermeneutic-phenomenological approach guided the research process, while a thematic analysis approach was used to analyze the interview transcripts. Our analysis revealed that clients who are asked to engage in the two-chair dialogue intervention often experience an embarrassment or awkwardness before they decide to engage. When engaged in the intervention, most clients found it intense and demanding, but also meaningful. A few clients found the intervention too intense to be of use. Many of those who participated reported that they became more aware of the fact that they were active agents who took part in their self-critical processes. The intensity and somewhat unusual nature of this intervention call for special attention to the working alliance before clients are invited to engage.